Multi-fractal Behaviors of long term daily relative humidity and temperature observed over Benin synoptic stations (West Africa) - Agbazo, Medard Noukpo; Gabin, Koton'Gobi; Basile, Kounouhewa; Eric, Alamou; Abel, Afouda; Norbert, Hounkonnou (Earth Sciences Research Journal, 2019)
The multifractal structure of daily temperature and relative humidity is investigated in this study. Multifractal Detrended Fluctuation Analysis (MFDFA) method has been applied on data observed from 1967 to 2012 at the six synoptic stations of Benin (Cotonou, Bohicon, Parakou, Save, Natitingou and Kandi). We estimate the generalized Hurst exponent, the Renyi exponent, and the singularity spectrum from the data to quantify the multi-fractal behaviors. The results show that multi-fractality exists in both daily humidity and temperature record at Benin synoptic stations. It shows multi-fractality with the curves of h (q), τ (q) and D (q), depending on the values of q. The comparison of the multifractal properties shows that, at all the synoptic stations, the multifractal strength of the temperature is significantly different from the feature the humidity. For the temperature, among the six study sites, the multifractal strength at Natitingou is largest (∆α = 0.6917). This means that Natitingou is the city in which the multifractal property is strongly observed for temperature. At Parakou the multifractal strength is smallest (∆α = 0.5252), meaning that Parakou is the city in which the multifractal property is weakly observed. At all synoptic stations the multifractal strength are superior to 0.5 (Δα> 0.5) indicating the degree of multifractal in temperature time series. For the relative humidity, multifractal strength is smallest Kandi (∆α = 0.3031). This means that Kandi is the city in which the multifractal property is weakly observed. Furthermore, the multifractal strength of Parakou is largest (∆α = 0.7691) meaning that for the relative humidity, Parakou is the city in which the multifractal property is strongly observed. The geographic distribution of the multifractal strength reflects the role of climate dynamic processes on the multi-fractal behavior of humidity and the distinctiveness of physical processes in Benin.